(untitled) (Research, Society and Development, 2021)
Currently, polymers have been reinforced with natural fibers, aiming at generating a class of new materials less aggressive to the environment. Therefore, this study aimed to develop biopolyethylene (BioPE)/cotton linter compounds, compatible with polyethylene grafted with maleic anhydride (PE-g-MA). The compounds were initially prepared in a co-rotational twin screw extruder, and thereafter, the extruded granules were injection molded. The compounds were characterized by mechanical properties (impact and traction), heat deflection temperature (HDT), Vicat softening temperature (VST), differential exploration calorimetry (CSD), contact angle and scanning electronic microscope (SEM). There was a slight increase in elastic modulus, tensile strength, HDT and VST of the compounds, compared to neat BioPE. However, there were losses in impact strength. The presence of PE-g-MA and the linter increased the degree of crystallinity of the compounds, compared to BioPE. The compatibilized compounds showed particles of linter connected with the BioPE matrix, indicating possible interactions between maleic anhydride and hydroxyl groups of the linter. Improved results were achieved when PE-g-MA was used with a higher degree of grafting, suggesting that functionalization impacts the mechanical and thermal properties of the compounds.